Unraveling historical knowledge: validation of the content of a historical skills assessment test - López-García, Alejandro; Zaragoza Vidal, María Victoria; Rodríguez-Medina , Jairo; Monteagudo Fernández, José (Revista Complutense de Educación, 2025)
INTRODUCTION. The assessment of historical thinking implies overcoming traditional tests that seek to assess the acquisition of conceptual content through the recall of facts, names, or relevant dates of the past. The new evaluative reality must move towards an emerging test model that places the demonstration of thinking skills at the center; that is, empathizing with the past and building bridges to contemporary situations, prioritizing rigor in historical selection, working with sources, causal argumentation in historical narratives, counterfactual dialectics, or ethical questioning of the past, among others. METHOD. Based on these aspirations, the aim of this work is to design and validate an alternative test to the EBAU in Spain, which allows the assess of the historical thinking skills acquired by students who complete the Baccalaureate stage. To this end, an assessment test on historical competencies has been developed. It is an instrument that has undergone a content validation process through an inter-judge process in four key dimensions, in which the Bangdiwala (BWN) and Gwet (AC2) weighted coefficients of concordance were applied. Once validated, it was optimized through a focus group with 10 experts in Social Science Didactics. RESULTS. The results were processed, analyzed, and considered for the construction of the final version, to which a peer review was applied with students from the Faculty of Education of the University of Murcia, in order to finalize the test and check its applicability. DISCUSSION. A standardized and useful instrument has been obtained for the assessment of historical skills in line with other proposals, aimed at helping Secondary Education teachers towards an innovative and transforming competency-based evaluation model.
Keywords: Baccalaureate; assessment; historical method; written examination